Academic trajectories of Chinese, Korean, Filipino, Mexican, and non-Hispanic White immigrants during high school and the impacts of social capital - Akira Kanatsu (ProQuest LLC, 2011)
This study investigated the trajectories of school GPA among immigrant youth during high school and the associations between these trajectories and financial, human, and social capital factors, after accounting for demographic differences. The sample consisted of 3,454 high school students (mean age = 14.51 year-old in the fall of 9th grade), who identified themselves as first- or second-generation Chinese, Korean, Filipino, Mexican, or White immigrants, as well as third-plus-generation White youth. Ethnic-generational variations in the latent factors (i.e., initial level and growth) of academic trajectories were first assessed between the third-plus-generation White youth, the reference group, and the ten immigrant groups, using Latent Growth Modeling (LGM). Generational variations were then examined within ethnic/racial groups. Finally, variations in academic trajectories were explored within ethnic/ethnic-generational groups using Latent Class Growth Analysis (LCGA). Once multiple trajectory classes were identified, multinomial logistic regression was used to test the associations between the trajectory classes and financial, human, and social capital factors, over and above demographic differences. The results of LGM models indicated higher initial GPAs among both generations of Chinese, Korean, and Filipino youth, lower initial GPAs among both generations of Mexican youth, and similar initial GPAs among both generations of White immigrant youth, compared to their third-plus-generation White counterparts. For the growth of GPAs, Asian youth had more negative, Mexican youth had somewhat more positive, and White immigrant youth had similar growth, compared to the reference group, which had slightly negative change over time. The capital factors did not explain the ethnic generational variations. Generational variations within ethnic groups were only found among Chinese, Koreans, and Filipinos. When such variations were found, first-generation youth had higher initial GPAs and more negative growth than their second-generation counterparts. Unlike the ethnic-generational variations, however, the generational variations in growth of GPAs were explained by the capital factors. The results of LCGA indicated 3 to 4 classes of academic trajectories in each ethnic/ethnic-generational group. They represented high, middle, and low achieving classes. Finally, the results of multinomial logistic regression indicated that some of the social capital factors were associated with the trajectory classes of Chinese and Korean youth.--Abstract.